A geometrical-numerical method for the determination of the acoustic field properties related to the directions of reflected waves - TAJCHERT, Maria (Archives of Acoustics, 1982)
A method for theoretical determination of the field in enclosures is presented. To analyse the directivity of the field, the spatial distributions of the directions of the reflected waves and their energy are calculated using the geometrical-numerical method. Diffusion coefficients of the directions, energy and ray energy are introduced. These coefficients characterize in general the directional properties of the field at a given point and determine in detail the values of energy reaching the observation point from different parts of the space. An algorithm for a computer program and the results of numerical calculations for a rectangular room which illustrate the effect of the different parameters of the source-room-observation point system on the directional properties of the field are given.